(untitled) (Swiss Medical Weekly, 2020)
Medication errors are among the most common medical adverse events and an important cause of patient morbidity and mortality, affecting millions of people worldwide each year. This problem is especially acute in paediatric settings, where most drugs given intravenously to children are provided in vials prepared for the adult population. This leads to the need for a specific, individual, weight-based drug-dose calculation and preparation for each child, which varies widely across age groups. This error-prone process places children at a high risk for life-threatening medication errors, particularly in stressful and critical situations, such as cardiopulmonary resuscitation. To limit and mitigate the likelihood of their occurrence, hospitals are increasingly adopting eHealth interventions aimed at supporting and securing each individual stage along the whole medication process, but there is mixed evidence regarding their positive contribution. These technologies are helpful as long as they are used within the scope of their application and users are aware of their limitations, as their introduction has sometimes led to new, often unforeseen, types of errors. The aim of the present work is to provide an overview of some of the main eHealth interventions used across the various stages of the medication process and to highlight areas that require attention in order to implement successful digital technologies. More specifically, the contribution of eHealth technologies in paediatrics is discussed, including the out-of-hospital setting, as well as barriers to their implementation in low- and middle-income countries. Finally, we describe our own work in this field with regards to the development and use of an innovative, evidence-based mobile device application (PedAMINES) to address the unmet need of reducing paediatric medication errors, especially during cardiopulmonary resuscitation. The PedAMINES app has also the potential to make a very effective contribution to the goals of the Third World Health Organization Global Patient Safety Challenge to reduce severe, avoidable medication-associated harm by 50% in all countries over the next 5 years, including low- and middle-income countries.